In vitro antifungal activities of 26 plant extracts on mycelial growth of Phytophthora infestans (Mont.) de Bary - Yanar, Yusuf; Kadioglu, Izzet; Gokce, Ayhan; Demirtas, Ibrahim; Goren, Nezhun; Cam, Halit; Whalon, Mark (ACADEMIC JOURNALS, 2011)
Antifungal activities of 26 plant extracts were tested against Phytophthora infestans using radial growth technique. While all tested plant extracts produced some antifungal activities Xanthium strumarium, Lauris nobilis, Salvia officinalis and Styrax officinalis were the most active plants that showed potent antifungal activity. They totally inhibited the mycelial growth of P. infestans. The other tested plant extracts exhibited moderate activity and average daily radial growth of fungus varied from 0.8 to 5.0 mm/day which were significantly lower than the control. The lowest antifungal activity was observed on Cynodon dactylon extract. The minimum inhibitory concentration (MIC) of the extracts ranged between 2 and 8% (w/v). X. strumarium extract produced the lowest MIC value of 2% which was lower than the standard fungicide Ridomil Gold mz 68 WP. Further studies on isolation and characterization of the active (antifungal) compound is needed before the possible use of the tested extracts in control strategies of this fungus.
Keywords: Plant extracts; Phytophthora infestans; antifungal; minimum inhibitory concentration (MIC); MATING TYPES; LATE BLIGHT; POTATO; METALAXYL; RESISTANCE; POPULATIONS; GENOTYPES; TOMATO; Biotechnology & Applied Microbiology